2014
DOI: 10.1038/eye.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Th17-associated cytokines in tears of patients with dry eye syndrome

Abstract: Purpose To determine the levels of Th17-associated cytokines, particularly interleukin (IL)-17 and IL-22 in tears of patients with dry eye syndrome. Methods Tear samples were collected from 20 healthy volunteers, 20 dry eye (DE) patients with non-Sjö gren's syndrome (NSSDE) and 20 DE patients with Sjö gren's syndrome (SSDE). Symptom questionnaire was self-administered and multiple dry eye disease (DED)-related clinical tests were performed. The levels of IL-17 and IL-22 in tears were measured by enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 20 publications
2
67
0
1
Order By: Relevance
“…Findings of Yoon et al[10] and Lam et al[17]showed that the level of IL-17 in tears from DED patients was increased. The correlation studies revealed associations between some of inflammatory mediators such as IL-6, IL-17 and IL-22 and ocular surface parameters[12, 13, 17]. However, few study specifically focused on Th17-associated cytokines and limited data have been published evaluating the expressions of cytokines in mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of Yoon et al[10] and Lam et al[17]showed that the level of IL-17 in tears from DED patients was increased. The correlation studies revealed associations between some of inflammatory mediators such as IL-6, IL-17 and IL-22 and ocular surface parameters[12, 13, 17]. However, few study specifically focused on Th17-associated cytokines and limited data have been published evaluating the expressions of cytokines in mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is now recognized that CD4 + T cells including T helper 1 (Th1) cells and T helper 17 (Th17) cells are thought to be the effector T cells and moreover, Th17 cells are primarily responsible for maintaining the chronic and relapsing course of the disease[7, 8]. Several studies have shown that increased levels of inflammatory cytokines such as interleukin (IL)-1, IL-6, IL-8 and tumor necrosis factor (TNF)-α found in tears[9–12], and Tan et al showed that IL-17 and IL-22, the effective cytokines of Th17 cells, significantly increased in tears of patients with DED[13]. Thus, inflammatory cytokines particularly Th17-associated cytokines may play roles in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Due to ethical and technical problems in histological studies of human lacrimal glands, tears represent a powerful tool to investigate pSS-dry eye. Although lacrimal IL-17 is increased in dry eye syndrome of different etiology in humans and animal models [75][76][77] such increase is significantly more pronounced in pSS patients compared to those with non-pSS dry eye syndrome. In addition, a parallel elevation of IL-6 has been also observed in pSS tears, suggesting an underlying loop to maintain Th17 response in lacrimal glands [76].…”
Section: Association Of Il-17/th17 Cells With Histological Pattern Anmentioning
confidence: 95%
“…2,69 A study examining the inflammatory cytokines IL-17 and IL-22 found that they were increased in patients with dry eye and positively correlated with dry eye questionnaire and keratopathy scores. 70 …”
Section: Presentation and Impact On The Ocular Surfacementioning
confidence: 99%